Spring‐Fall Asymmetry in VLF Amplitudes Recorded in the North Atlantic Region: The Fall‐Effect. Issue 16 (10th August 2021) - Macotela, E. L.; Clilverd, M.; Renkwitz, T.; Chau, J.; Manninen, J.; Banyś, D.
Abstract: A spring‐fall asymmetry is observed in daytime amplitude values of very low frequency (VLF) radio wave signals propagating over the North Atlantic during 2011–2019. We explore the processes behind this asymmetry by comparing against mesospheric mean temperatures and the semidiurnal solar tide (S2) in mesospheric winds. The solar radiation influence on VLF subionospheric propagation was removed from the daytime VLF amplitude values, isolating the fall‐effect. Similarly, the symmetric background level was removed from mesospheric mean temperatures undertaking comparable analysis. During fall, all three analyzed parameters experience significant deviation from their background levels. The VLF amplitude variation during spring is explained by the seasonal variation in solar illumination conditions, while the fall‐effect can be interpreted as a mean zonal wind reversal associated with both a S2 enhancement, and temperature reductions. Decreases in temperature can produce decreases in collision frequency, reducing VLF signal absorption, driving the observed VLF asymmetry. Plain Language Summary: The ionosphere is useful for it makes long‐distance radio communication possible. Its lower boundary is called the D‐region (60–90 km) and can be monitored using the very low frequency technique, VLF for short. VLF radio signals propagate long distances in the Earth‐ionosphere waveguide. Monitoring the annual variability of the signal's amplitude measured in Northern Finland during daytime, a comparative amplitude asymmetry during spring and fall seasons is observed, for which the responsible mechanism is still unknown. Here, we report a multiyear analysis of this asymmetry observed using VLF signals propagating at middle‐to‐high latitudes. Around the D‐region altitudes, the sun induces oscillations in the wind dynamics called solar tides. At the same altitudes, the mesospheric mean temperature has the unique characteristic of a cool summer and a warm winter. We put forward the hypothesis that, during fall, the mean zonal wind reverses from westerly to easterly, and this is associated with both semidiurnal solar tide enhancement, and mean temperature changes. The latter can affect the chemistry and dynamics in the D‐region in a significant way, eventually changing the VLF propagation condition, and therefore, the amplitude strength. Key Points: Long‐term monitoring of daytime very low frequency (VLF) amplitudes shows a spring‐fall asymmetry with unexpected enhancements during fall Mean annual temperature at 70–80 km, with removed symmetric level, shows a deviation during fall that anticorrelates with the VLF behavior The semidiurnal solar tide amplitude at 70–80 km is also enhanced during fall, suggesting the influence of a mean zonal wind reversal